A caça e a pesca na beira de Tabatinga: um estudo do mercado de recursos naturais na tríplice fronteira Brasil - Colômbia - Peru - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
The network of protein market at the border region makes up a highly complex reality beco- ming difficult to visualize the assemblages given the illegality of the flows. This research is an interdisciplinary dialogue and represents a market approach from the actor-network theory of Bruno Latour and consisted in an attempt to describe this network, making this approach de- cisive to the research progress. The issue of the network of protein market and its relationship with the cities is an approach not only owned by Economy and Geography, but is also about the environment, especially when it touches the Amazon theme, particular in the study area - the triple border between Brazil, Colombia and Peru - where access to protein is directly linked to the use of natural resources, by the intense consumption of fish and bushmeat.In this way the study aims to answer the following question: What is the relationship between the price of game meat and the access to natural resources at the network established by the trade of protein in the study area? Starting from these questions we proposed some specific objec- tives: I - Describe the construction of the bushmeat marketing network in the triple border as from the illegality and the use of natural resources; II - identify and describe the actors and controversies on the social groups formation on the network of bushmeat trade; III -describe the relationship between bushmeat, their substitutes and seasonality in order to identify how the use of natural resource occurs. To describe the network of animal protein market it was conducted a preliminary field research in March, May and September 2013 in Atalaia do Norte, Benjamin Constant, Tabatinga and Caballococha (Peru) to collect preliminary data, pre-test the methodology and especially obtain trust of the actors. In 2014 a long visit in Tabatinga was held between May and November, following the actors of the network.The use of semi-structured and open interviews with merchants and regular visitors to the Beira (i.e., the river bank, where happens most of the commercial activities) was adopted, as well as fish monitoring in the Beira which resulted in the collection of 2,106 samples of ‘sartas’ (i.e., local measuring system) of various fish, representing the supply of the Beira marreteiros (i.e., local mediator). For bushmeat monitoring it was used a registration form of sales of wildlife and also the participant observation. Among the main results obtained, is highlighted the im- portance of fish trade at the border, which wins international market traits in the parallel mar- ket level; the importants regional and international flows of illegal bushmeat market, which can’t be neglected, and its intimate and contradictory relationship with fishing and the prohi- bition beyond the description of the relationships of the illegal market of game and the control in the Beira of Tabatinga and the use of natural resources.
Keywords: Recursos Naturais; Mercado ilícito; Tríplice fonteira amazônica; CIÊNCIAS AGRÁRIAS